Des compétences clés européennes au Socle commun français : importation d’un nouveau paradigme et réaffirmation des fondamentaux de l’École républicaine - Jean-François Nordmann (Éducation et Socialisation)
A comparative reading of the French decree relative to the ‘Common Base of knowledge and skills’ (Socle commun de connaissances et de compétences) (11-7-2006) and the ‘Proposal for a Recommendation of the European Parliament and of the Council on key competences for lifelong learning’ (10-11-2005) confirms that one of the major sources of the French decree is the text of the European Proposal, which provides its architecture and general theoretical frame and inspires numerous formulations. But this comparison also brings forth that the French decree undertakes an important rewriting work which deeply modifies its spirit and allows a reassessment of the fundamental educational missions proper to French Republican school. In this respect, the reconfigurations within the statement of the 6th and 7th French competences are particularly significant as well as those regarding the 5th competence.